Estimating the number of preventable cardiovascular disease events in the United States using the EMPA-REG OUTCOME trial results and National Health and Nutrition Examination Survey. (July 2020) - Wong, Nathan D; Fan, Wenjun; Pak, Jonathan
Aim: We examined eligibility and preventable cardiovascular disease events in US adults with diabetes mellitus from the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME). Methods: We identified adults with diabetes mellitus eligible for EMPA-REG OUTCOME based on trial eligibility criteria available from the National Health and Nutrition Examination Surveys, 2007–2016. We estimated composite cardiovascular disease endpoints, as well as all-cause deaths, death from cardiovascular disease and hospitalizations for heart failure from trial treatment and placebo event rates, the difference indicating the preventable events. Results: Among 29, 629 US adults aged ⩾18 years (representing 231.9 million), 4672 (27.3 million) had diabetes mellitus, with 342 (1.86 million) meeting eligibility criteria of EMPA-REG OUTCOME. We estimated from trial primary endpoint event rates of 10.5% and 12.1% in the empagliflozin and placebo groups, respectively, that based on the 'treatment' of our 1.86 million estimated EMPA-REG OUTCOME eligible subjects, 12, 066 (95% confidence interval: 10, 352–13, 780) cardiovascular disease events could be prevented annually. Estimated annual preventable deaths from any cause, cardiovascular causes and hospitalizations from heart failure were 17, 078 (95% confidence interval: 14, 652–19, 504), 14, 479 (95% confidence interval: 12, 422–16, 536) and 9467 (95% confidence interval: 8122–10, 812), respectively. Conclusion: Empagliflozin, if provided to EMPA-REG OUTCOME eligible US adults, may prevent many cardiovascular disease events, cardiovascular and total deaths, as well as heart failure hospitalizations.